2017
DOI: 10.7150/thno.21216
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Stimulating Hormone Accelerates Atherogenesis by Increasing Endothelial VCAM-1 Expression

Abstract: Rationale: Postmenopausal atherosclerosis (AS) has for decades been attributed to estrogen deficiency. Although the follicular stimulating hormone (FSH) levels rise sharply in parallel, the direct effect of FSH on AS has never been investigated. In this study, we explored the possible role of FSH in the development of AS.Methods: This was a prospective cohort study of 48 healthy premenopausal and 15 postmenopausal women. ApoE knockout mice were used as atherosclerosis model and human umbilical vascular endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 57 publications
1
47
1
Order By: Relevance
“…Postmenopausal status is characterized by high levels of FSH and LH, as well as low levels of E2, making it difficult to explore the precise role of FSH in renal function in the OVX mouse model. To diminish the potential effect of these two parameters, we used GnRHa‐treated ovariectomized mice administered with recombinant FSH in accordance with several studies (Li, Chen, et al, ; Song et al, ). Given that kidney injury is a relatively chronic process, we increased the dose of FSH from 0.15 IU to 0.3 IU and lengthened intervention time to 6 weeks, which was different from Liu's study on fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal status is characterized by high levels of FSH and LH, as well as low levels of E2, making it difficult to explore the precise role of FSH in renal function in the OVX mouse model. To diminish the potential effect of these two parameters, we used GnRHa‐treated ovariectomized mice administered with recombinant FSH in accordance with several studies (Li, Chen, et al, ; Song et al, ). Given that kidney injury is a relatively chronic process, we increased the dose of FSH from 0.15 IU to 0.3 IU and lengthened intervention time to 6 weeks, which was different from Liu's study on fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FSHR was specifically localized in caveolae of endothelial cells. Caveolin-1, the main protein component of caveolae, directly interacted with FSHR and mediated its downstream signaling actions [36].…”
Section: Effects Of Fsh On Endothelial Cell Activation and Atherosclementioning
confidence: 99%
“…"Epidemiological and animal studies have revealed that FSH contributes to the decline in bone health in women undergoing menopausal transition. Emerging data has shown that FSH treatment enhances atherosclerotic plaque formation in ovariectomized AopE -/mice [36]. However, our understanding of the molecular mechanisms through which FSH increases the risk of osteoporosis and cardiovascular disease is far from complete (see outstanding questions)."…”
Section: )mentioning
confidence: 99%
“…Total RNA was isolated from tissues and PTFs with Trizol or Purelink RNA mini kit for reverse transcription and PCR amplification as described previously (Cui et al, ; Li et al, ). PCR primers were as folllows: (a) for MMP‐9, 5′‐GCGTCTTCCCCTTCACTTTC‐3′ (Forward) and 5′‐ATAGGGTACATGAGCGCCTC‐3′ (Reverse); (b) for HuR, 5′‐CCAACTTGTACATCAGCGGG‐3′ (Forward) and 5′‐GGCTGCAAACTTCACTGTGA‐3′ (Reverse); (c) for glyceraldehyde 3‐phosphate dehydrogenase (GAPDH), 5′‐GTCAGTGGTGGACCTGACCT‐3′ (Forward) and 5′‐TGCTGTAGCCAAATTCGTTG‐3′ (Reverse).…”
Section: Methodsmentioning
confidence: 99%
“…bio-rad.com/en-us/product/quantity-one-1-d-analysis-software; RRID:SCR_014280.) 2.12 | RT-PCR and quantitative real-time PCR analysis Total RNA was isolated from tissues and PTFs with Trizol or Purelink RNA mini kit for reverse transcription and PCR amplification as described previously (Cui et al, 2016;Li et al, 2017). PCR primers were as folllows:…”
Section: Gelatin Zymographymentioning
confidence: 99%